2007
DOI: 10.1016/j.ijpara.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Pf34, a novel GPI-anchored rhoptry protein found in detergent-resistant microdomains

Abstract: Apicomplexan parasites are characterised by the presence of specialised organelles, such as rhoptries, located at the apical end of invasive forms that play an important role in invasion of the host cell and formation of the parasitophorous vacuole. In this study, we have characterised a novel Plasmodium falciparum rhoptry protein, Pf34, encoded by a single exon gene located on chromosome 4 and expressed as a 34 kDa protein in mature asexual stage parasites. Pf34 is expressed later in the life cycle than the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…The existence of raft-like domains with distinct properties has been previously proposed for late endosomes, which contain cholesterol-rich microdomains both in their limiting membrane and in intraluminal vesicles (51). It was also shown that the fractionation patterns for two falciparum detergent-resistant rhoptry proteins differ, suggesting that multiple DRM populations exist within this organelle (52).…”
Section: Drm Rafts In Malaria Parasite Infection and Pathogenesis-mentioning
confidence: 66%
“…The existence of raft-like domains with distinct properties has been previously proposed for late endosomes, which contain cholesterol-rich microdomains both in their limiting membrane and in intraluminal vesicles (51). It was also shown that the fractionation patterns for two falciparum detergent-resistant rhoptry proteins differ, suggesting that multiple DRM populations exist within this organelle (52).…”
Section: Drm Rafts In Malaria Parasite Infection and Pathogenesis-mentioning
confidence: 66%
“…To determine whether PfRON6 was localised within rhoptries or micronemes, double labelling experiments with anti-RAMA (a rhoptry marker), anti-Pf34 and anti-PfRON4 (rhoptry neck markers), and anti-AMA1 (a microneme marker) antibodies were performed (Fig. 4C) (Bannister et al, 2003; Topolska et al, 2004; Alexander et al, 2006; Proellocks et al, 2007). We analysed 10 images for each antibody pair and quantified co-localisation using Pearson’s coefficient (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exceptions to this include rhoptry-associated membrane antigen (55), Pf34 (43), and apical sushi protein (19,41). Interestingly, the GPI-anchored proteins Pf38 (45) and MSP10 (4) have been suggested to have both surface and apical distributions.…”
Section: Discussionmentioning
confidence: 99%